Combined mepacrine–hydroxychloroquine treatment in patients with systemic lupus erythematosus and refractory cutaneous and articular activity. (September 2018) - Ugarte, A; Porta, S; Ríos, R; Martinez-Zapico, A; Ortego-Centeno, N; Agesta, N; Ruiz-Irastorza, G
Aim: The aim of this study was to evaluate the clinical response to combined therapy with hydroxychloroquine and mepacrine in patients with systemic lupus erythematosus and refractory joint and/or skin disease. Methods: Mepacrine was added to 46 systemic lupus erythematosus patients unresponsive to treatment with the following drug combinations: hydroxychloroquine + prednisone + immunosuppressive drugs ( n = 24), hydroxychloroquine + prednisone ( n = 16), hydroxychloroquine + prednisone + retinoids ( n = 2), hydroxychloroquine alone ( n = 1), hydroxychloroquine + one immunosuppressive drug ( n = 1), hydroxychloroquine + prednisone + one immunosuppressive drug + belimumab ( n = 1) or hydroxychloroquine + prednisone + belimumab ( n = 1). The outcome variable was the clinical response, either complete or partial, based on clinical judgement. The Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) and the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score were additionally used. Results: A total of 91% patients showed complete/partial response, with similar rates among those with joint or skin disease. In patients with cutaneous activity, a statistically significant decrease in the CLASI was seen. There also was a statistically significant decrease in the SLEDAI. The mean daily dose of prednisone decreased from 5.8 to 3.4 mg/d ( p = 0.001). Prednisone could be discontinued in 20% of patients. No serious adverse events were seen. Smoking was the only predictor of complete response. Conclusion: In the setting of refractory skin and/or joint disease, the addition of mepacrine to previous therapy including hydroxychloroquine was safe and effective in reducing disease activity and decreasing prednisone doses. The fact that smokers responded better opens the door to further studying the combination of mepacrine–hydroxychloroquine as a first-line therapy in such patients.